Evaluation of the performance of e-commerce using the analytic hierarchy process (AHP): business perspectives on e-commerce / Sid Sirisukha - Sirisukha, Sid (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2017)
The purpose of this study is to employ the Analytic Hierarchy Process (AHP) to evaluate electronic commerce (e- commerce) types. An important contribution of this study is the identification of business perspectives on e-commerce types. This study articulates distinctive characteristics of the types of e- commerce and management processes that extend the range of applicability across diverse business segments. The Analytic Hierarchy Process (AHP) helps the decision maker such as business executives to prioritize alternatives in B2B, B2C, and C2B as e- commerce types, so that the best one can be selected. As business innovation has relied increasingly on partnerships between business and supplier, there is a different perspective of how business executives view their business process and competitive advantage. Based on the findings from this study, one important way for business people to be heard is to devote their time to create competitive advantage and develop shared domain knowledge which appear as the most influential construct in the AHP model. Business executives need to understand the leverage points of the industry, the history and current issues of the e-commerce, and to learn to apply business- oriented objectives in the application of technology to gain competitive advantage. This change in view would help focus their attention on e-commerce technology and ideas that will produce the most benefit and create competitive advantage, rather than those that offer the most technical promise.